Motivating factors that influence class F contractors to become entrepreneurs - Nor Aishah Buang,; Yufiza Mohd Yusof, (penerbit ukm, 2006)
The purpose of this study is to find out what are the motivating factors that influence class F contractors to become entrepreneurs. Those motivating factors include family background, education background, and psychological factors such as sense of freedom, satisfaction, innovation, success, recognition and important roles. The conceptual framework for this study was adapted from the Entrepreneurship Education and Development Process Model. Interviews and questionnaires were used to collect the data. Statistical analysis such as frequency, percentage, t-test, Pearson correlation, and one-way ANOVA were used. The findings suggested that business family background, education level and other psychological factors not necessarily serve as the motivating factors for the class F contractors to choose to become entrepreneurs. The conclusion that can be made from these findings is this type of business is unique in terms of the usual motivating factors that influence individuals to become entrepreneurs. In the case of class F contractors, exposure to the corresponding experiences and specific trainings in the relevant business area are more important motivating factors that encourage them to become entrepreneurs.